OFDM spectral precoding with per-subcarrier distortion constraints - Khawar Hussain; R. López-Valcarce (European Signal Processing Conference (EUSIPCO), 2019)
Spectral precoding is effective in reducing out-of-band radiation (OBR) in multicarrier systems, but it introduces distortion in the data, requiring a suitable decoder at the receiver. Thus, trading off OBR reduction, implementation complexity, and error rate is of paramount importance. We present a precoder design which minimizes OBR under constraints on the distortion at each individual data subcarrier. By judiciously choosing the distortion profile, the decoding task can be significantly alleviated, with a sizable improvement in terms of implementation complexity with respect to previous designs.
Keywords: spectrum shaping; winter